Investigate of usage of water as blast mitigator for high impact penetrator - Mohd Shamer Mohd Mokhtar (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This project is about investigating the usage of water as a blast mitigator for high impact penetrator. The higt impect penetrator is an apparatus that uses to accelerate the projectile at high velocity. The shaped charge concept is used in this project to make sure the projectile can accelerate at high velocity. The explosive charge that is used in this project is Emulex. The concept of water consumption is used in high-impact penetration to ensure it can withstand the pressure of high explosives.